Challenges in prenatal diagnosis of agenesis of cavum septum pellucidum and septo optic dysplasia - Trajkova, Jasmina; Rambabova, Marija; Milunovikj, Sanja; Tilev, Zoran; Pushevski, Vladimir; Kocevska, Ana; Ismaili, Bashkim; Shpishikj Pushevska, Anamarija (Macedonian Medical Association = Македонско лекарско друштво, 2024)
Agenesis of the Septum Pellucidum (ASP), a rare neurological disorder, is frequently associated with Septo-Optic Dysplasia (SOD). This condition is marked by the absence of the septum pellucidum and can include symptoms like optic nerve hypoplasia and hypopituitarism, presenting significant diagnostic challenges. This report focuses on a 25-year-old expectant mother. The initial diagnosis was uncertain, but comprehensive neurosonography eventually disclosed the nonexistence of septum pellucidum leaflets. At 22 weeks, a second ultrasound raised suspicions of corpus callosum agenesis and mild ventriculomegaly. Further advanced imaging at 35 weeks revealed an agenesis of septum pellucidum, thin corpus callosum and the presence of chiasma opticum, visualized using 3D transvaginal tomographic ultrasound imaging (TUI). This comprehensive approach underlines the need for detailed examinations in such complex cases. The mother opted against undergoing amniocentesis. The MRI was carried out, yet its interpretation was not completed. The patient successfully delivered a full-term, healthy baby. Post-delivery, the newborn underwent extensive pediatric evaluations and was referred for specialized follow-up, considering the prenatal findings. This case contributes significantly to the limited yet critical research on ASP and SOD. It highlights the difficulties in distinguishing isolated ASP from SOD based on initial symptoms and the variability in prognosis. Isolated ASP generally predicts a more favorable outcome, whereas SOD can lead to more severe conditions. ASP and SOD present intricate challenges in both diagnosis and management. Accurate identification of the cavum septum pellucidum is vital for assessing neurological development. Varied prognoses in such cases necessitate employing comprehensive diagnostic techniques, including MRI, amniocentesis, and advanced ultrasound imaging, to ensure precise diagnosis and effective management.
Keywords: cavum septum pellucidum; prenatal diagnosis; septo-optic dysplasia